A physiotherapist-led biopsychosocial education and exercise programme for patients with chronic low back pain in Ghana: a mixed-methods feasibility study - Ampiah, Paapa Kwesi (2023)
Background Low back pain (LBP) is a common musculoskeletal disorder which causes substantial years lived with disability globally and in Sub-Saharan Africa. The biopsychosocial (BPS) model of management has been recommended in national and international practice guidelines for the management of chronic low back pain (CLBP) and has also demonstrated to be effective in clinical research. However, this clinical research has been predominantly delivered in high income countries (HICs), although evidence suggests that the prevalence of LBP is substantially higher in low- and middle-income countries (LMICs) especially in Africa (39%; 95% CI 30 – 47). Understanding the effectiveness of BPS interventions in LMICs especially in Africa is a very underexplored area, with substantial inequity between research from HICs and LMICs. Ghana is a LMIC where the effectiveness of BPS interventions for the management of CLBP has been underexplored. The aim of this PhD was therefore to establish the feasibility of delivering a physiotherapist-led BPS programme for the management of patients with CLBP in a Ghanaian context.